2020
DOI: 10.21776/ub.jiip.2020.030.02.08
|View full text |Cite
|
Sign up to set email alerts
|

Feeding combination of Lactobacillus casei and extracts of dahlia tuber or garlic on intestinal bacteria, nutrients digestibility and performance of broiler chickens

Abstract: This study aimed to evaluate the effect of dietary inclusion of 2% synbiotic (Lactobacillus casei + dahlia tuber extract/LEDT or Lactobacillus casei + garlic extract/LEGT) on intestinal bacteria, nutrient digestibility, and growth of broiler chickens. A total of 150 birds of one-day-old male Cobb broiler were randomly assigned into three groups of treatment with five replications (10 birds each). Dietary treatments applied were T0 = basal ration, T1 = basal ration + 2% LEDT, T2 = basal ration + 2% LEGT. Synbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The amount of ration consumption and the number of excreta measured. Nutrient digestibility measured according to Mangisah et al [8] as follows:…”
Section: Data Collectionmentioning
confidence: 99%
“…The amount of ration consumption and the number of excreta measured. Nutrient digestibility measured according to Mangisah et al [8] as follows:…”
Section: Data Collectionmentioning
confidence: 99%
“…Inulin, a soluble dietary fiber, cannot be digested or hydrolyzed by a digestive enzyme of poultry. However, inulin can be fermented by Lactobacillus casei together with endogenous LAB producing healthy intestinal conditions indicated by low coliform growth (Mangisah et al, 2020). A previous study indicated that the improvement of body health with better meat quality and low cholesterol content in crossbred local chicken was due to the modulation effect of inulin derived from dahlia tuber (Fajrih et al, 2014).…”
Section: Introductionmentioning
confidence: 99%